2006
DOI: 10.2337/dc06-0242
|View full text |Cite
|
Sign up to set email alerts
|

All Pre-Diabetes Is Not the Same: Metabolic and Vascular Risks of Impaired Fasting Glucose at 100 Versus 110 mg/dl

Abstract: T he dramatic increase in incidence of diabetes (1) has prompted efforts to identify individuals who have milder glucose intolerance, because early management with lifestyle change and/or medication can delay progression to diabetes with its attendant morbidity, mortality, and cost (2). It has long been recognized that impaired glucose tolerance (IGT) is a diabetes precursor, but recognition of IGT requires oral glucose tolerance tests (OGTTs), which many health care providers are reluctant to order (3). As a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Human blood plasma and erythrocyte samples were received frozen on dry ice from the Screening for Impaired Glucose Tolerance (SIGT) study 28 via the National Institute for Diabetes and Digestive and Kidney Diseases Central Repository. Samples were divided into three groups by the SIGT based on the results of the OGTT: normal glucose tolerance (NGT), impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM).…”
Section: Methodsmentioning
confidence: 99%
“…Human blood plasma and erythrocyte samples were received frozen on dry ice from the Screening for Impaired Glucose Tolerance (SIGT) study 28 via the National Institute for Diabetes and Digestive and Kidney Diseases Central Repository. Samples were divided into three groups by the SIGT based on the results of the OGTT: normal glucose tolerance (NGT), impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM).…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the IFG110 group, the IFG100 subjects showed no difference in BP and lipid profiles, although they were found to have greater AG. More recently, Tai et al [17] and Phillips et al [21] reported that IFG100 subjects exhibited a higher percentage of clinical features for metabolic syndrome. In 8-year follow-up study of Tai and colleagues [17], IFG100 subjects were also found to be at greater risks for developing diabetes and ischemic heart diseases than those with NFG and NGT.…”
Section: Discussionmentioning
confidence: 97%
“…20,22 Finally, the cumulative effects of metabolic abnormalities (e.g., hypertension and/or dyslipidemia together) are not considered. 23 Thus, existing tools likely result in high false-positive and false-negative rates in American young adults.…”
Section: Introductionmentioning
confidence: 99%